2016
DOI: 10.1590/s0102-865020160100000005
|View full text |Cite
|
Sign up to set email alerts
|

Is the combination of fat grafts and platelet rich plasma effective in rats?

Abstract: PURPOSE:To investigate if the association of fat grafts and platelet-rich plasma (PRP) improves graft viability in female rats. METHODS:This is an experimental, randomized and blinded study, which involved 47 rats. Fat was harvested from the inguinal region and grafted to the cranial region. The experimental group consisted of PRP-enriched fat grafts (n=22) whilst the control group consisted of fat graft only (n=25). After a 100-day period, the animals were euthanised and the fat grafts were analyzed using sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Pires Fraga et al [26,27] studied the effect of PRP on the survival of free fat grafts in a rabbit model and demonstrated that the application of autologous PRP could enhance free fat graft survival. Blumenschein et al [28] also confirmed the efficacy of fat grafts prepared with PRP in maintaining graft volume and survival in a rat model. Cervelli et al [29,30] used 0.3-0.5 mL PRP mixed with 1 mL centrifuged fat tissue for reconstructing the face contour and restoring the superficial density of facial tissues, and the examinations after 18 months showed excellent aesthetic improvement.…”
Section: Discussionmentioning
confidence: 81%
“…Pires Fraga et al [26,27] studied the effect of PRP on the survival of free fat grafts in a rabbit model and demonstrated that the application of autologous PRP could enhance free fat graft survival. Blumenschein et al [28] also confirmed the efficacy of fat grafts prepared with PRP in maintaining graft volume and survival in a rat model. Cervelli et al [29,30] used 0.3-0.5 mL PRP mixed with 1 mL centrifuged fat tissue for reconstructing the face contour and restoring the superficial density of facial tissues, and the examinations after 18 months showed excellent aesthetic improvement.…”
Section: Discussionmentioning
confidence: 81%
“…The ease of comparison of animal studies, as with clinical studies, is made difficult by the wide variety in methodology including differences in PRP preparation technique and source, fat harvest and preparation methods, constitution of PRP, and different graft sites. Despite this, there have been several animal studies that have shown a benefit to graft retention in contouring procedures with PRP being shown to enhance the vascularity and reduce fat necrosis of transplanted fat . In a rat model, one study found that activated PRP enhances fat graft retention as well as the survival, viability, and differentiation of adipocytes .…”
Section: Prp and Fat In Animal Studiesmentioning
confidence: 99%
“…Despite this, there have been several animal studies that have shown a benefit to graft retention in contouring procedures with PRP being shown to enhance the vascularity and reduce fat necrosis of transplanted fat. [174][175][176][177] In a rat model, one study found that activated PRP enhances fat graft retention as well as the survival, viability, and differentiation of adipocytes. 178 Pires Fraga et al also found that PRP not only improved graft retention but also maintained a higher number of adipocytes and blood vessels with reduced necrosis and fibrosis in a rabbit model.…”
Section: Prp and Fat In Animal Studiesmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) positively promotes the induction of pluripotent stem cells in adipocytes [8].…”
Section: Introductionmentioning
confidence: 99%